Globalization and the Future of Social Protection - Tanzi, Vito (IMF Working Papers; Working Paper, 2000)
Social protection in industrial countries has been provided through regulations, tax expenditures, and public spending. This paper argues that globalization will affect governments' ability to continue providing this social protection at the level of recent decades. Specifically, tax competition among jurisdictions, ballooning electronic commerce, and increased mobility of the factors of production will likely cause significant falls in tax revenue in future years. The paper concludes that the welfare states need to look for alternative ways to provide social protection.